(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article examines the influence of the type and amount of modifiers on the properties of secondary thermoplastics. The classification and sources of waste formation of high molecular weight materials are given. The physical and chemical properties of plastics are analyzed. Particular attention is paid to composite materials. The features of obtaining mixtures for the manufacture of compositions based on crushed and modified waste are noted.